Frequency and nature of complications after lung resections for tuberculosis in HIV-infected patients - D. V. Alkaz; T. S. Basek; Yu. I. Pashina; D. Sh. Dzhamshedov; A. M. Panteleev; А. V. Elkin (Вестник хирургии имени И.И. Грекова)
The objective of this work was to study the frequency and nature of complications after lung resections for tuberculosis in HIV-infected patients.Material and methods. Retrospective and prospective analysis of complications after lung resections for tuberculosis in 80 HIV-infected and 117 HIV-negative patients was carried out. Developed complications are divided into nonspecific and specific complications, according to the modified Russian classification of postoperative complications on the basis of Accordion classification.Results. It was noted that among the operated HIV-infected patients, XDR-TB (extensive drug-resistant tuberculosis) and clinically significant concomitant diseases were more common. Differences in the frequency of intraoperative complications in groups have not been established. Postoperative complications were mostly disposable, the frequency of deaths in the main group did not differ from that in the comparison group.Conclusion. Surgical treatment of pulmonary tuberculosis in HIV-infected patients is reasonable and justified, in general for patients with pulmonary tuberculosis, with adequate antituberculous chemotherapy and antiretroviral therapy.